Analisis Kombinasi Bakteri Lactobacillus lactis dan Lactobacillus bulgaricus terhadap Protein dan Lemak Keju Susu Kerbau (Bubalus bubalis) selama Masa Simpan - Sari, Linda; Nasution, Rizki Amelia; Selvia, Irda Nila (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Buffalo milk (Bubalus bubalis) has a high protein and fat content and lower cholesterol than cow's milk, but this nutritional content causes a relatively short shelf life so that further processing is required, one of which is to make cheese. During the shelf life, the quality of cheese can decrease due to microbial activity, enzymatic reactions, and protein and fat degradation. Lactobacillus lactis and Lactobacillus bulgaricus bacteria produce proteolytic enzymes that can modify the protein and fat content in cheese. This study aims to analyze the effect of the combination of Lactobacillus lactis and Lactobacillus bulgaricus bacteria on the protein and fat content of buffalo milk cheese at different shelf lives. The study used four treatments without repetition with shelf lives of 1, 7, and 14 days. Protein content was analyzed using the Kjeldahl method and fat content using the Soxhlet method. Data on pH, water content, total LAB, protein content, and fat content were analyzed descriptively quantitatively, while organoleptic tests were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test (p<0.05). The results showed that the combination of bacteria increased protein and fat content as the shelf life increased, with the highest values ??being 47.44% and 32.94%, respectively, accompanied by a decrease in pH and total LAB. In conclusion, the addition of 3% Lactobacillus lactis and 3% Lactobacillus bulgaricus can improve the quality of buffalo milk cheese. This research contributes to the science of food fermentation regarding the role of the combination of Lactobacillus lactis and Lactobacillus bularicus bacteria on the chemical characteristics of buffalo milk cheese during shelf life.